DEVELOPING STUDENTS’ STARTUP BUSINESS THROUGH IMPLEMENTATION OF ENTREPRENEURIAL LEARNING MODEL - Jony Oktavian Haryanto; Donald Samuel Slamet Santosa; Andi Ina Yustina; Rendika Nugraha (President University, 2021)
This community service starts from difficulties of university students in Indonesia to develop start up business. Most of the students make business in food and beverages, although they are not majoring in culinary art, food technology, or other food based major. The problem indicate that students have no good entrepreneurial spirit. To solve the problem, this program will use other method in developing students’ startup business, namely Entrepreneurial Learning Model (ELM). The steps of ELM are: training, education, experience, and mentoring. This model has already run for 6 months (May to October 2019) to 10 groups of students (who make 10 startup business). The results of this program are: (1) students able to develop their startup business; (2) the startup business come from their innovative idea; and (3) students able to maintain their business. Based on the results, it is recommended to use the model on developing students’ startup business.